Profiling microorganisms in whole saliva of children with and without dental caries. Issue 4 (20th June 2019) - Vieira, Alexandre R.; Hiller, N. Luisa; Powell, Evan; Kim, Leon Hak‐Jin; Spirk, Tracy; Modesto, Adriana; Kreft, Rachael
Abstract: Objectives: Dental caries is a highly prevalent infectious disease that causes tooth decay. While no single bacterial species is causative of dental caries, the role of the oral microbiome in oral health and caries is gaining interest. The purpose of this study is to compare the major species present in whole saliva samples from caries‐free and caries‐active children using the IBIS Universal Biosensor. Material and Methods: The abundant microbial species in ninety‐five whole saliva samples from caries‐free and caries‐active subjects were characterized using the IBIS Universal Biosensor. Results: Twenty‐four genera and sixty‐five species were detected. Candida and Streptococcus were common across samples, and often the dominant genus. While we did not observe a strong association between the most abundant species and oral health, Bacteroides thetaiotaomicron and Rothia mucilaginosa were enriched in children with active caries; while, Staphylococcus epidermidis was enriched in caries‐free children. Conclusions: These study trends observed suggest that microbial markers in saliva may serve as predictors of oral health and thus aid in diagnosis and treatments for prevention of caries. Consistent with competitive interactions, we also observed negative associations between Streptococcus pneumoniae and other streptococcal species, Staphylococcus aureus and S. epidermidis, Candida and Neisseria, and Saccharomyces and Streptococcus .